Everyday opinions in news discussion forums: Public vernacular discourse. (October 2017) - Johansson, Marjut
Highlights: News discussions as a space of everyday opinions. News discussion forum as content-based online discussion. Public vernacular discourse derived from the private space of users. Public vernacular discourse contains affective and unconfirmed information. Abstract: In this paper, news discussion forums are studied as vernacular public discourse and as a communicative genre in the digital context. First, these forums are defined as a vernacular public discourse since users base their reasoning on private sphere stancetaking, and their views do not receive legitimation. Additionally, the participants comprise a hybrid public that shares networking but not necessarily a common ground on the topic being discussed. Second, news discussion forums are based on the communicative activity of commenting as they are initiated by a news article or other types of professional news content. They can be compared to content-based and knowledge-based discussions in social media, but they have their own specific characteristics. Third, the users do not necessarily reveal their source of knowledge, but when they do, references are of a general nature or they are anchored in the private sphere of the participants.